2018
DOI: 10.3390/en12010041
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and CFD Modelling: Impact of the Inlet Slug Flow on the Horizontal Gas–Liquid Separator

Abstract: For a gas-liquid separator sizing, many engineers have neglected the flow pattern of incoming fluids. The impact of inlet slug flow which impeded onto the separator’s liquid phase will cause a separator fails to perform when sloshing happened in the separator. To date, the study on verifying the impact of inlet slug flow in a separator remains limited. In this paper, the impact of inlet momentum and inlet slug flow on the hydrodynamics in a separator for cases without an inlet device were investigated. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…and increasing the gas flow rate from 1.5 to 9 𝑚 3 ℎ , slug flow occurs as shown in Figure 6-E. Considering that the slug flow regime has been observed in the flow pipeline, it is important to investigate possible control methods in the laboratory pilot to manage this regime [9,12].…”
Section: Resultsmentioning
confidence: 99%
“…and increasing the gas flow rate from 1.5 to 9 𝑚 3 ℎ , slug flow occurs as shown in Figure 6-E. Considering that the slug flow regime has been observed in the flow pipeline, it is important to investigate possible control methods in the laboratory pilot to manage this regime [9,12].…”
Section: Resultsmentioning
confidence: 99%
“…What’s more, Liu et al (2018a, 2018b) explored the thermal stratification in the liquid hydrogen tank by setting a series of gravity values. Lee et al (2018) discussed the influence of the inlet slug flow on the horizontal gas-liquid separator. Some scholars (Zheng et al , 2018; Liu et al , 2018a, 2018b) had done a research about liquid sloshing in a 2D tank by installing different kinds of complex baffles inside the container, and they found that the complex baffles could play an important role in reducing the dynamic pressure.…”
Section: Introductionmentioning
confidence: 99%